2012
DOI: 10.1016/j.tetlet.2012.03.066
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric α-hydroxy ketone synthesis by direct ketone oxidation using a bimetallic palladium(II) complex

Abstract: Chiral α-hydroxy ketones (acyloins) are important intermediates for the asymmetric synthesis of natural products, fine chemicals, and drugs. 1 For that reason, their enantioselective synthesis is of considerable interest and there have been a number of reports with various approaches to chiral α-hydroxy ketones. 2 One general approach involves the preparation of enolates or enol derivatives, 3 while another method involves catalytic asymmetric oxidation of (E)-enol phosphates by (salen) Mn(III) complexes. 4 A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Henry and Becker reported that ketones are hydoxylated without previous enol formation by a binuclear palladium complex with a triketone acting as bridging ligand (Scheme 9). 57 Benzoin was obtained in moderate yield (52%), but with high enantioselectivity (87% ee). A catalytic amount of trifluoroacetic acid was required, possibly to promote the formation of the enol.…”
Section: Scheme 8 Sharpless -Hydroxylation Of Silyl Enol Ethersmentioning
confidence: 97%
“…Henry and Becker reported that ketones are hydoxylated without previous enol formation by a binuclear palladium complex with a triketone acting as bridging ligand (Scheme 9). 57 Benzoin was obtained in moderate yield (52%), but with high enantioselectivity (87% ee). A catalytic amount of trifluoroacetic acid was required, possibly to promote the formation of the enol.…”
Section: Scheme 8 Sharpless -Hydroxylation Of Silyl Enol Ethersmentioning
confidence: 97%
“…[126] In contrast, hydrogen peroxide acts both as the regenerator of active Pd species and as the source of hydroxide in the procedure reported by Jung's team, which uses tridentate carbenic Pd II complexes in association with AgBF 4 . [128] Cyclopentanone and cyclohexanone were αand -hydroxylated in low yields [Equation (124)]; no more than 9 % yield was attained from other ketones. [128] Cyclopentanone and cyclohexanone were αand -hydroxylated in low yields [Equation (124)]; no more than 9 % yield was attained from other ketones.…”
Section: Hydroxylationmentioning
confidence: 99%
“…Heating butyric acid at reflux in MeOH with PhI(OAc) 2 and Pd(OAc) 2 catalyst did not afford the methoxylation product, [80] whereas use of Jung's system [Equation (124) [127] ] led to a mixture of the three corresponding hydroxy acids [Equation (133)]. [127,128] The enantioselective formation of 3-hydroxybutanoic acid in the presence of a chiral catalyst indicates that palladium intermediates are really associated with the hydroxylation process.…”
Section: Carboxylic Phosphinic and Phosphonic Acidsmentioning
confidence: 99%
“…Traditional methods to prepare α-acetoxy ketones are the acetolysis of α-diazo ketone (Newman and Beal, 1950 ; Erickson et al, 1951 ; Corey and Knapp, 1976 ; Kitamura et al, 2012 ; Wang et al, 2014 ; Tan et al, 2016 ; Yuan et al, 2016 ; Zhang et al, 2016 ; Hu et al, 2018 ), α-bromo ketone (Tanner et al, 1991 ; Valgimigli et al, 2003 ; Ahmed and Langer, 2006 ; Chen et al, 2013 , 2016 ; Nolla-Saltiel et al, 2014 ; Carneiro et al, 2015 ; Liu et al, 2016 ; Yuan et al, 2019 ), and in situ generated α-iodo derivatives (Du et al, 2015 ; Ren et al, 2016 ; Chen et al, 2017 ; Tan et al, 2017 ; Pogaku et al, 2019 ), which usually require the pre-functionalization of ketones ( Scheme 1A ). In contrast, umpolung reactions have taken a prominent place for the direct α-oxygenation of carbonyl compounds via oxidation of the enolates or related derivatives with transition metal complexes (Littler, 1962 ; Heiba and Dessau, 1971 ; Ng and Henry, 1976 ; Rubottom et al, 1983 ; El-Qisairi and Qaseer, 2002 ; Hamed et al, 2012 ), or hypervalent iodine reagents (Mizukami et al, 1978 ; Nicolaou et al, 2002 ; Bogevig et al, 2004 ; Sunden et al, 2004 ; Ochiai et al, 2005 ; Huang et al, 2007 ; Yu et al, 2010 ; Izquierdo et al, 2016 ; Arava et al, 2017 ) ( Scheme 1B ). Metal-free hypervalent iodine compounds as classical oxidative functionalization reagents have attracted considerable interest due to a variety of advantages relative to conventional oxidants such as heavy metals (Pb, Tl, or Hg), including low toxicity, ready availability, mild conditions, excellent selectivity, and a comparable reactivity (Du et al, 2015 ; Ren et al, 2016 ; Chen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%